2019
DOI: 10.4314/sajas.v49i5.4
|View full text |Cite
|
Sign up to set email alerts
|

Growth, carcass and meat quality traits of two South African meat rabbit breeds

Abstract: Rabbits could contribute to meat production in South Africa. However, little research has been done on rabbit farming in the country, including on the performance of locally available meat breeds. This study examined the meat production of the New Zealand White (NZW) and Phendula rabbit breeds. The live weights (LW) and average daily gains (ADG) of 80 (44 male, 36 female) NZW and 40 (22 male, 18 female) Phendula rabbits, housed in single-sex groups of three, were recorded from weaning (5 weeks) until slaughter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…Therefore, the slightly higher IMF content in hind leg meat of MS sired rabbits was not different from that found in H rabbits. However, the IMF content of LTL meat was higher in males of the present study, which also was observed ( p ˃ 0.05) by North et al [ 38 ] in the LTL of meat rabbit genotypes. It seems that male rabbits may in some cases deposit more IMF into the LTL muscle with advancing age.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the slightly higher IMF content in hind leg meat of MS sired rabbits was not different from that found in H rabbits. However, the IMF content of LTL meat was higher in males of the present study, which also was observed ( p ˃ 0.05) by North et al [ 38 ] in the LTL of meat rabbit genotypes. It seems that male rabbits may in some cases deposit more IMF into the LTL muscle with advancing age.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the male springhare showed slightly higher values for their forearms (~98 g vs.~91 g), LTL (~227 g vs.~195 g), HL (~650 g vs.~614 g) and tails (~67 g vs.~65 g) compared to the female springhare; a trend to note in future studies. Similar results were seen for meat rabbits where the male animals tended to have heavier weights for the different cuts compared to females [22]. Furthermore, it is possible that the lack of sex effect could be linked to age, but due to sampling bias, it was not possible to determine the age of the animals during the night cull.…”
Section: Carcass Characteristicssupporting
confidence: 61%
“…As springhares breed year-round, breeding breaks or associated changes in body weight due to pregnancy or changes in body condition were not apparent. The weights were the same as those reported for New Zealand and Phendula meat rabbits [22]. Mature springhares typically weigh 3-4 kg [23,24], which are at the higher end of the dead weights recorded for the springhare of this study (Table 1).…”
Section: Carcass Characteristicsmentioning
confidence: 58%
“…Rabbit meat is good for health and differs from other meats by its taste and dietary properties. The ability to use fresh frozen rabbit meat in all seasons enhances its dietary properties [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the direction of production, rabbits are divided into two groups, namely meat and meat skins. In the meat direction, rabbits are slaughtered at 60-70 days of age, and in the meat-skin direction at 3-5 months of age [5]. Each mother rabbit can give birth to 5-6 times a year.…”
Section: Introductionmentioning
confidence: 99%